(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
Estimation of the age of living persons is required in many civil and criminal cases and in questionable cases. Registration of birth certificate is the most reliable document as an evidence of real age, but for many reasons, births are not registered in many cases in India, especially in the rural areas. This requires various radiological investigations to be carried out to estimate the age. In rural settings, these facilities are not available and, if available, are limited to the use for patients who are in more need of such medical facilities. Thus, physical examination involving secondary sexual characteristics promises to be an easy and cost-effective means for the same purpose. The objectives of this study were: (1) to find out the age of appearance of various secondary sexual characteristics in adolescent males and females; (2) to note the ages of development of various stages of such characteristics; and (3) to find the maximum age after which a specific characteristic is universally present. The study involved the examination of adolescents of both the sexes, aged between 12 and 20 years, coming to the Out patient department (OPD) of the Forensic Medicine Department of the PBM Hospital and from the population residing around the campus. A total of 165 subjects (109 males and 56 females) were examined to study the appearance and development of various secondary sexual characteristics. Breast development started before the age of 12 years and most girls aged between 12 and 13 years exhibited stage A development. All girls aged above 17 years showed stage D development. Pubic hairs were in stage A in 90% of the girls aged between 12 and 13 years and 100% girls beyond 17 years exhibited stage D development. Axillary hairs were present in 100% subjects aged above 16 years. In males, pubic hairs appeared later than in females, but were present in all cases above 14 years and were in stage D in boys aged above 17 years. Axillary hairs appeared between 14 and 15 years of age in all the cases. Adam’s apple became prominent between 14 and 16 years of age in all the cases and facial hairs appeared between 15 and 16 years of age. Secondary sexual characteristics could be utilised as a definite procedure for age estimation within a narrow age range in maximum number of cases, thus saving time, energy and resources. Remaining doubtful cases could be solved with more sophisticated methods, like radiological examination and dental analysis, requiring special diagnostic tools and specialised personnel. Though some regional variations were seen in secondary sexual characteristics, as were seen in other methods too, these could be easily worked out by undertaking regional research and setting the standards.